The Effect of Different Combinations of Calcium Hydroxide as Intra-Canal Medicament on Endodontic Pain: A Randomized Clinical Trial Study - Ghanbarzadegan, Arash; Ajami, Majid; Aminsobhani, Mohsen (Iranian Endodontic Journal, 2019)
Introduction: After treating the tooth root canal, pain is one of the problems that many patients are facing. In order to reduce pain, and regarding the advice of treating necrotic teeth during several sessions, intra-canal medicaments can be used between sessions. The purpose of this study is to compare pain relieving effect of calcium hydroxide combined with three solutions of normal saline, chlorhexidine 2% and dexamethasone. Materials and methods: This triple blind randomized clinical trial was performed on 90 necrotic molars and premolars. The patients were classified in three medicaments' groups including mixture of calcium hydroxide and normal saline (G1), chlorhexidine 2% (G2) or dexamethasone (G3) that were placed in the canal during the first treatment session. The patients were provided with a Heft-Parker Visual Analog Scale form to record their pain in different intervals of 4, 24, 48, 72 and 96 h after cleaning and shaping the root canal. Data analysis was carried out using the Chi-Square, one-way ANOVA and Repeated Measure tests. Results: No significant difference was observed in the mean pain of the groups after 4 h (P>0.05). However, a significant difference was found between G1 and G3 in the mean pain from day 1 to 72 h after treatment. The mean pain was less in dexamethasone (G3) group (P<0.05), but the difference was not statistically significant at 96 h after treatment (P>0.05). No significant difference was found between "G2-G1" and "G2-G3" groups at different time intervals (P>0.05). Conclusion: The mixture of calcium hydroxide and dexamethasone compared to calcium hydroxide and normal saline in short and medium time had a significant effect on reducing pain after cleaning and shaping the root canal. It seems that the mixture of calcium hydroxide and dexamethasone can be considered as an effective medicament on reducing pain during root canal treatment sessions. Keywords: Root Canal Therapy; Postoperative Pain; Dexamethasone; Calcium Hydroxide, Chlorhexidine